2018
DOI: 10.1002/ejic.201800383
|View full text |Cite
|
Sign up to set email alerts
|

1D and 2D Polybromotellurates(IV): Structural Studies and Thermal Stability

Abstract: Three novel polybromotellurates(IV) were obtained by reactions of TeO 2 in conc. HBr with Br 2 and tri-or tetraalkylammonium salts. They contain [TeBr 6 ] 2octahedra connected by {Br 2 } linkers into one-or pseudo-two-dimensional networks.[a] Nikolaev

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Thus, the QTAIM parameter values together to the RDG analysis, for both theoretical levels, indicate the van der Waals character of this interaction. The values obtained for Br•••Br at BCPs presented here are consistent for non-covalent interactions involving Br atoms obtained in previous studies [20,37,38].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the QTAIM parameter values together to the RDG analysis, for both theoretical levels, indicate the van der Waals character of this interaction. The values obtained for Br•••Br at BCPs presented here are consistent for non-covalent interactions involving Br atoms obtained in previous studies [20,37,38].…”
Section: Resultssupporting
confidence: 91%
“…Currently, QTAIM and RDG approaches have found large applicability for the study of many electronic properties, particularly in the study of weakly interacting systems [69][70][71][72]. Recently, the combination of these two methods was found to be useful on description of the intermolecular halogen interactions [37,73].…”
Section: Computational Studiesmentioning
confidence: 99%
“…For estimation of the energies of Cl⋅⋅⋅Cl XB, we followed the protocol applied by us for relevant polyhalide hybrids earlier [20, 37] (DFT calculations using experimentally obtained atomic coordinates, followed by QTAIM analysis [38] ). Depending on the method (see SI for details), E int values vary within the 2.2–2.7 kcal mol −1 range for 1 (abovementioned disordering in the structure of 2 did not allow us performing corresponding calculations).…”
Section: Figurementioning
confidence: 99%
“…According to the TGA data, the mass loss corresponding to full eliminationo f{ Cl 2 }b egins above 100 8C; destruction of (Me 4 N) 2 [TeCl 6 ]" matrix" occurs within 310-360 8Cr ange. The reason of this "anomaly" is not fully clear;h owever, we can suggest that it can be related to more extended network of H•••Cl interactions in 2 (see Supporting Information, Figure S3 For estimation of the energieso fC l•••Cl XB, we followed the protocola pplied by us for relevant polyhalide hybrids earlier [20,37] (DFT calculations using experimentally obtained atomic coordinates,f ollowed by QTAIM analysis [38] ). Depending on the method (see SI for details), E int values vary within the 2.2- In summary,w eh ave shown that the methodology of halogen bonding-assisted "trapping" of di-or polyhalides by halometalatesc an be expanded on dichlorine derivatives as well, and this approachc an lead to unusually stable supramolecular compounds.…”
mentioning
confidence: 99%
“…(besides, other mechanisms of di- or polyhalogen uptake by coordination compounds also exist). On the other hand, in our recent works we showed that the formation of polyhalide–halometates is a general feature for p-block elements including bismuth­(III), , antimony­(V), and tellurium­(IV), and these compounds demonstrate fascinating structural diversity: dihalogen or, more rarely, polyhalogen fragments connect halometalate anions into one-dimensional (1D), two-dimensional (2D), or even three-dimensional (3D) supramolecular associations. Apart from the fundamental importance of these findings in terms of inorganic (interestingly, these studies coincided with great progress in the research of polyhalides per se ), supramolecular, and structural chemistry, an additional argument in favor of further investigations in this area is related to halometalate-based solar cells, which represent one of the “hot topics” in modern materials science. Indeed, it can be assumed that the presence of di- or polyiodide units in the structure can be favorable in terms of relevant physical properties.…”
Section: Introductionmentioning
confidence: 99%